Poverty and Social Impact Analysis : A Suggested Framework - Hossain, Shahabuddin (IMF Working Papers; Working Paper ;, 2003)
Following the adoption by the international community of the Poverty Reduction Strategy Paper (PRSP) approach, which provides the basis for concessional lending by the multilateral institutions, there has been a resurgence of interest in the poverty and social impact analysis (PSIA) of different policy reforms being considered by the low income countries. This paper reviews some of the major techniques and frameworks for assessing the PSIA. It highlights their strengths and weaknesses and suggests a relatively simple analytical framework for the PSIA based on household survey data. The paper then shows how the suggested framework could be utilized to investigate the poverty/income distributional implications of introducing a value-added tax (VAT). The results indicate that a revenue-neutral uniform VAT is regressive in its impact on different households. In order to mitigate the adverse impact, the paper explores the distributional impact of an alternative policy package consisting of a basic rate of VAT with exemptions and excise taxes for certain commodity groups chosen on the basis of their distributional characteristics. The distributional consequences of the alternative package are found to be superior to those of the uniform VAT.